Temozolomide Induced Hypermutation in Glioma: Evolutionary Mechanisms and Therapeutic Opportunities - Daniel, Paul; Sabri, Siham; Chaddad, Ahmad; Meehan, Brian; Jean-Claude, Bertrand; Rak, Janusz; Abdulkarim, Bassam S. (Frontiers in Oncology, 2019)
Glioma are the most common type of malignant brain tumor, with glioblastoma (GBM) representing the most common and most lethal type of glioma. Surgical resection, radiotherapy and chemotherapy using the alkylating agent Temozolomide (TMZ), remain the mainstay of treatment for glioma. While this multimodal regimen is sufficient to eliminate the bulk of tumour, recurrence is inevitable and often poses major challenges for clinical management due to treatment resistance and failure to respond to targeted therapies. Improved tumour profiling capacity enabled characterization of the genomic landscape of gliomas with the overarching goal to identify clinically relevant subtypes and inform treatment decisions. Increased tumour mutational load has been shown to correlate with higher levels of neoantigens and is indicative of the potential to induce a durable response to immunotherapy. Following treatment with TMZ, a subset of glioma have been identified to recur with increased tumour mutational load. Identification of hypermutation state in glioma following treatment with TMZ suggests that hypermutation may represent a subtype of recurrence with unique molecular vulnerabilities. In this review, we will elaborate on the current knowledge regarding the evolution of hypermutation in gliomas and the potential therapeutic opportunities that arise with TMZ-induced hypermutation in gliomas.